حق الرجوع على الشريك في المال الشائع في حالة الانتفاع والتصرف - عبدالرضا, حسين عبدالله; صالح, قتيبة مهدي (Journal of Legal Sciences, 2017)
The  subject of the  right of return on  partner on common property  in  the  case of the use and disposition  from  the important  subjects in the real property rights,  the  importance  lies through  by identifying  the  band  which  Allows  by  law to  the partner initiate authorities which  conferred  him of the right of  ownership to share  common if  the  low is not allowed to exceed  this  range by any partner because it  infects the right of others partners hence arises it is then  established  to the  other partner  right  back  to the  infringer  Partner.  Through  find the  subject of  study  show cases  which  form  infringement of the other partner and  form this  cases have   a partner  the right  of  return to  the  other partner  who  benefited or  disposal  in property  common which  is permitted  by law.  The common partner if  he was allows by the  law to  use his  common  share  and exploited  and dispose of  them .that is  showed be in legal limits which  means it showed be amount the  common  share if the partner utilize  or acted  by  or  more than his  common  share or all the common property or  caused by directly authority of the  use and disposition in damage  for  the  rest of  the  partners in  such  cases was to the another partner directly his  share stake in the  back  overtaking  or cause.